Biomaterial-assisted drug delivery for interstitial cystitis/bladder pain syndrome treatment. Issue 1 (12th November 2020) - Lin, Zhijun; Hu, Hanze; Liu, Bolong; Chen, Yanyan; Tao, Yu; Zhou, Xiangfu; Li, Mingqiang
Abstract : This review aims to highlight emerging biomaterial-assisted drug delivery systems for interstitial cystitis treatment and provide a perspective on future developments. Abstract : Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic and painful bladder condition afflicting patients with increased urinary urgency and frequency as well as incontinence. Owing to the elusive pathogenesis of IC/BPS, obtaining effective therapeutic outcomes remains challenging. Current administrational routes such as intravesical-bladder injection improve the treatment efficacy and reduce systemic side effects. However, the bladder permeability barrier hinders drug penetration into the bladder wall to meet the desired therapeutic expectation. These issues can be addressed by encapsulating drugs into biomaterials. When appropriately exploited, they would increase the drug dwelling time in the bladder, enhance the penetration of mucosa and improve the therapeutic response of IC/BPS. In this review, we first elucidate the pathogenesis and animal models of IC/BPS. Then, we highlight recent representative biomaterial-assisted drug delivery systems for IC/BPS treatment. Finally, we discuss the challenges and outlook for further developing biomaterial-based delivery systems for IC/BPS management.